Eksistensi Autonomous Weapons Berbasis Artificial Intelligence Dalam Konflik Bersenjata - Dalie Muhammad Za'im; Hesti Septianita (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This normative legal research examines the compatibility of Lethal Autonomous Weapons Systems (LAWS) with International Humanitarian Law (IHL). Although principles of distinction, proportionality, and humanity apply, fundamental normative gaps exist due to AI's limitations in moral and contextual judgment. The findings highlight serious accountability challenges in state responsibility attribution under the ILC 2001 framework caused by the systems' autonomous nature. The study recommends establishing a binding international legal instrument at the 2026 CCW Review Conference and encourages active Indonesian diplomacy in regulating autonomous weapons globally to ensure compliance with humanitarian principles.